Is survival influenced by metastatic site in synchronous metastatic pancreatic adenocarcinoma (PDAC)? A prospective real-world BACAP study - E. Alouani; C. Canivet; B. Bournet; L. Buscail; J. Selves; B. Napoleon; L. Palazzo; N. Flori; P. Guibert; A.-C. Brunac; C. Maulat; F. Muscari; et al. (ESMO Gastrointestinal Oncology)
Background: Advanced pancreatic ductal adenocarcinoma (PDAC) carries a dismal prognosis with a 5-year survival rate of 3%. While treated as an even population, previous retrospective studies suggested significantly different survival rates for patients with lung-only metastases when compared with other patients. This study aims to explore prospectively the difference in survival outcome based on initial site of metastases in synchronous metastatic PDAC. Patients and methods: This is a prospective observational study including all adult patients with synchronous metastatic PDAC in BACAP (national Anatomo-Clinical Database on Pancreatic Adenocarcinoma). Data regarding patients’ demographics, tumor characteristics and survival outcomes were analyzed. Results: Overall, 559 patients were included (52.8% male, mean age 69 years) of which 26 (4.7%), 65 (11.6%), 299 (53.5%) and 169 (30.2%) patients had lung-only, peritoneal-only, liver-only and multi-site metastases at diagnosis, respectively. The median overall survival (OS) was significantly different according to metastatic site (P < 0.001) with a median OS for lung-only, peritoneum-only, liver-only and multi-site of 12.6 months [95% confidence interval (CI) 9.7-16.9 months], 8.6 months (95% CI 5.4-11.5 months), 7.9 months (95% CI 6.5-8.9 months) and 4.5 months (95% CI 3.9-5.8 months), respectively. The median progression-free survival (PFS) was also significantly different according to metastatic site (P < 0.01) with a median PFS of 6.3 months (95% CI 2.7-9.1 months), 5.1 months (95% CI 3.7-6.2 months), 4.7 months (95% CI 3.3-5.7 months) and 3.2 months (95% CI 2.6-4.1 months), respectively. Conclusions: Patients with lung-only metastases represented 4.7% of synchronous metastatic PDAC patients and exhibited improved survival. These results suggest that a subset of patients with synchronous metastatic PDAC could benefit from more aggressive locoregional treatments.